Atmospheric degradation, mechanism and kinetics of ethyl vinyl ketone (CH2=CHCOCH2CH3) initiated by Cl atom: an insight from DFT study. (3rd July 2022) - Yadav, Ajay Kumar; Mishra, Bhupesh Kumar; Singh, Ashutosh; Gour, Nand Kishor
Abstract : The mechanism and kinetics of the H-abstractions of ethylvinylketone (CH2 =CHCOCH2 CH3 ) with Cl atom have been carried out using density functional theory (DFT). The electronic structures and frequencies of reaction species are carried out at M06-2X/6-31+G(d, p) level. The energy calculation is performed for optimised species at the same functionality but using a 6-311++G(d, p) basis set. We characterised transition states (TSs) in each H-abstraction channel and explored reaction species along with TS involved in CH2 =CHCOCH2 CH3 +Cl reaction on the potential energy diagram. Among the various H-abstraction channels, H-abstraction from the methylene group (–CH2 –) of CH2 =CHCOCH2 CH3 is found to be a more dominant reaction channel which is further confirmed by thermochemical analysis. The rate constants of all H-abstraction reaction channels and overall rate constant are calculated using canonical transition state theory (TST) within the temperature range of 200–400 K. The value of the overall rate constant at 298.15 K and 1atm pressure is found to be 0.94 × 10 −10 cm 3 mol −1 s −1, which is in close with the experimental reported rate constant value, i.e. (2.91 ± 1.10) × 10 −10 cm 3 mol −1 s −1 . The percentage branching ratios of each H-abstraction reaction channel, as well as the lifetime of the titled compound, are also reported herein. GRAPHICAL ABSTRACT: UF0001